Water-stop breathable composite needle-punched fabric and preparation method thereof

By adopting a three-layer structure of water-stop and breathable composite needle-punch cloth, the problem of wear and peeling of the surface fibers of the car foot pad is solved, and the functions of breathability, water-stop and wear resistance are achieved, extending the service life and improving durability.

CN119872039APending Publication Date: 2025-04-25JIAXING HUALI NON WOVEN FABRIC CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510022934.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the long-term use and frequent friction of existing automotive foot pad products, the fibers on the surface may wear and fall off, causing the surface to become sparse and uneven, affecting durability.

Method used

The water-stop and breathable composite needle-punching cloth with a three-layer structure includes a 60-100g/m2 needle-punching non-woven fabric on the upper layer, a 30-120μm thickness PE/PA/PE co-extruded film on the middle layer and a 200-400g/m2 needle-punching non-woven fabric on the lower layer. This structural design realizes the functions of breathability, water-stop and wear resistance.

Benefits of technology

The composite needle-punch cloth combines breathability, water retention and wear resistance, extends service life, can resist external wear and tear, and achieves lightweight and efficient waterproof and breathable functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231923120000111
    Figure BDA0005231923120000111
  • Figure BDA0005231923120000121
    Figure BDA0005231923120000121
Patent Text Reader

Abstract

The invention belongs to the technical field of non-woven fabrics, and particularly discloses a water-stop breathable composite needle-punched fabric and a preparation method thereof. The waterproof breathable composite needle-punched fabric comprises an upper layer, a middle layer and a lower layer, the upper layer is a needle-punched non-woven fabric with the gram weight of 60-100g / m < 2 >, the middle layer is a PE / PA / PE co-extrusion film with the thickness of 30-120m, and the lower layer is a needle-punched non-woven fabric with the gram weight of 200-400g / m < 2 >. The water-stopping breathable composite needle-punched cloth prepared by the invention combines the breathability of the upper layer, the water stopping property of the middle layer and the supporting property of the lower layer, realizes the functions of breathability and water stopping, has good wear resistance, has a longer service life, and can resist external wear and tearing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nonwoven fabrics, and in particular to a water-stopping and breathable composite needle-punched fabric and a preparation method thereof. Background Art

[0002] Non-woven fabric, also known as non-woven fabric, non-woven fabric, needle-punched cotton, needle-punched non-woven fabric, etc., is a fabric that does not require spinning and weaving. It is a textile staple fiber or filament that is oriented or randomly arranged to form a fiber mesh structure. It has the characteristics of flexibility, moisture-proof, breathable, light weight, low price, and recyclability. It is widely used in car floor mats.

[0003] Existing car floor mat products are made of composite needle-punched cloth. After multiple compression and needle-punching processes, they have a tight fiber structure and therefore have high strength and durability. However, car floor mats need to withstand frequent trampling and friction. Under long-term use and frequent friction, the fibers on their surface may wear out or even fall off, causing the surface of the floor mat to become sparse and uneven, affecting the durability of the floor mat. Summary of the invention

[0004] In order to improve the problem of surface wear caused by long-term use of car floor mats, the present application provides a water-stopping and breathable composite needle-punched cloth and a preparation method thereof.

[0005] The present application provides a water-stopping and breathable composite needle-punched fabric, which adopts the following technical solution: A water-stopping and breathable composite needle-punched fabric, comprising an upper layer, a middle layer and a lower layer, wherein the upper layer has a gram weight of 60-100g / m 2 The middle layer is a PE / PA / PE co-extruded film with a thickness of 30-120μm, and the lower layer is a 200-400g / m 2 Needle-punched nonwoven fabric.

[0006] By adopting the above technical solution, the upper layer adopts 60-100g / m 2 The needle-punched non-woven fabric has the characteristics of high fiber density and high toughness, large internal gaps and non-sticky surface; the upper layer of needle-punched non-woven fabric ensures the air permeability of the whole system, so that the gas inside the system can be discharged smoothly to avoid the accumulation of moisture or heat inside; and the wear resistance of the needle-punched non-woven fabric can prevent the occurrence of tearing, wear and tear, and extend the service life of the whole system.

[0007] The middle layer is a PE / PA / PE co-extruded film with a thickness of 30-120μm. It has good waterproof, moisture-proof and barrier properties. As a waterproof layer, it can effectively block water penetration, ensure the water-stopping performance of the overall system, and block other liquids and impurities to keep the inside of the system clean and dry.

[0008] The lower layer uses 200-400g / m 2 The needle-punched non-woven fabric has a larger gram weight and provides stronger support and protection. The lower layer of needle-punched non-woven fabric increases the overall thickness and strength of the system, providing better support and stability; it can also protect the middle layer of co-extruded film from external damage and extend the service life of the overall system.

[0009] The waterproof and breathable composite needle-punched cloth prepared in the present application combines the air permeability of the upper layer, the waterproofness of the middle layer and the support of the lower layer, achieving the unique functions of being both breathable and waterproof. The needle-punched non-woven fabric has good wear resistance, which makes the composite needle-punched cloth have a long service life and can resist external wear and tear; through its unique three-layer structural design, it achieves multiple functions such as breathability, waterproofing, and wear resistance.

[0010] Preferably, the method for preparing the needle-punched nonwoven fabric comprises the following steps: (1) mixing polyester chips, epoxy linseed oil, calcium carbonate, isooctyl p-dimethylaminobenzoate, cerium dioxide, and an antioxidant at 70-80° C. to obtain a polyester fiber raw material, melt spinning at 350-360° C. to obtain polyester fiber filaments, combing and web-laying the polyester fiber filaments into a non-woven fabric semi-finished product, needle-punching and consolidating the polyester fiber filaments, and heat-setting the polyester fiber filaments to obtain a pre-treated non-woven fabric; (2) The pretreated nonwoven fabric of step (1) is immersed in an impregnation liquid at a temperature of 60-65° C. for 5-8 min, and then coagulated, washed, dried, and finally oiled to obtain a needle-punched nonwoven fabric.

[0011] By adopting the above technical scheme, polyester chips are converted into fibers through melt spinning. Epoxidized linseed oil has good heat resistance, light resistance, interpenetration and low-temperature flexibility, which improves the heat resistance, light resistance and mechanical strength of the fiber; calcium carbonate improves the mechanical properties and durability of polyester fibers, and isooctyl dimethylaminobenzoate has strong UV resistance, which improves the UV stability of polyester fibers. Cerium dioxide improves the heat resistance, oxidation resistance or UV stability of polyester fibers. Antioxidants are used to prevent polyester fibers from being degraded due to oxidation during processing and use, thereby extending the service life of the fibers. Polyester fibers are obtained by melt spinning, combed to form a thin and uniform fiber web, and the web is laid into a non-woven semi-finished product, and needle-punched to strengthen the bonding force between fibers, improve the strength and stability of the non-woven fabric, and obtain a pre-treated non-woven fabric with stable dimensions.

[0012] The pre-treated non-woven fabric is immersed in the impregnation liquid, which can be coated on the surface of the non-woven fabric to improve the durability, waterproofness, antibacterial properties and other characteristics of the non-woven fabric. The impregnated non-woven fabric is solidified to solidify the resin in the impregnation liquid and form a stable structure inside the non-woven fabric. The remaining impregnation liquid components and impurities are removed by water washing to ensure the purity and quality of the product. The drying treatment removes moisture and makes the non-woven fabric reach the required dryness for subsequent processing and use. The oiling treatment can form a protective film between the oil and the fibers, so that the fibers have a stronger bonding force, thereby enhancing the toughness, tensile strength, waterproofness and oil resistance of the material, making it more durable.

[0013] Needle-punched nonwoven fabrics made of polyester raw materials can be recycled and granulated and spun again, which saves raw material resources, reduces environmental pollution, and reduces costs. These materials have a high recycling value. Through recycling, discarded needle-punched fabrics can be converted into new raw materials, thereby saving raw material resources. If these wastes are directly discarded without treatment, they will cause pollution to the soil, water sources, etc., but through recycling, these wastes can be converted into valuable resources. Through recycling and reuse, companies can reduce the purchase of new raw materials, thereby reducing production costs.

[0014] Preferably, the raw materials of the impregnation solution include the following components: 20-25 parts of silane coupling agent KH-560, 16-19 parts of modified flax fiber, 6-10 parts of nano titanium dioxide, 18-22 parts of waterborne epoxy resin curing agent, 12-15 parts of modified montmorillonite, and 60-70 parts of deionized water.

[0015] By adopting the above technical solution, silane coupling agent KH-560 has epoxy functional groups and is an excellent adhesion promoter that can improve the dispersibility of the system and improve the adhesion with a variety of materials. Silane coupling agent KH-560 acts as a bridge to firmly combine the needle-punched non-woven fabric with other components in the impregnation liquid, thereby improving the strength and durability of the impregnated non-woven fabric. The modified flax fiber is loaded in the non-woven fabric to enhance the toughness and wear resistance of the impregnated non-woven fabric. At the same time, the modified flax fiber also has certain moisture absorption and air permeability, which helps to improve the wearing comfort and performance of the impregnated non-woven fabric.

[0016] Nano titanium dioxide has the effects of anti-ultraviolet, antibacterial, whitening and anti-aging. Nano titanium dioxide can be evenly distributed on the surface of non-woven fibers to form a protective layer, which improves the anti-ultraviolet, antibacterial and aging resistance of the impregnated non-woven fabric. The water-based epoxy resin curing agent can react with the functional groups on the surface of the non-woven fibers to form chemical bonds, thereby improving the crosslinking degree and strength of the impregnated non-woven fabric. At the same time, the water-based epoxy resin curing agent can also give the impregnated non-woven fabric good heat resistance, chemical resistance and electrical insulation properties. Modified montmorillonite has a large specific surface area and cation exchange properties, which can adsorb and remove impurities and pollutants on the surface of non-woven fibers. Moreover, modified montmorillonite can also be used as a filler and loaded on the surface of non-woven fabrics to improve the density and strength of the impregnated non-woven fabrics. The impregnation liquid composed of various components adheres to the surface of the non-woven fabric, which increases the mechanical properties, wear resistance, antibacterial and air permeability of the non-woven fabric.

[0017] Preferably, the method for preparing the modified flax fiber comprises the following steps: (1) crushing the flax fiber, dispersing it in a sodium hydroxide solution, stirring it at a temperature of 80-85° C. for 2-3 hours, washing it with water, and then dispersing it in hydrochloric acid, immersing it at room temperature for 12-14 hours, washing it with water, and drying it to obtain pretreated flax fiber; (2) dispersing the modified graphene in deionized water, adding the pretreated flax fiber of step (1), ultrasonicating for 2-3 hours, filtering, and drying to obtain a mixture; (3) Dispersing chitosan in acetic acid solution, adding isopropanol, stirring at room temperature for 5-8 minutes to obtain a mixed solution, spraying the mixed solution into the mixture obtained in step (2), and drying to obtain modified flax fiber.

[0018] By adopting the above technical scheme, the flax fiber is crushed, and the sodium hydroxide can react with the colloid substance in the flax fiber to decompose it and expose the cellulose, and the sodium hydroxide remaining on the fiber and the impurities generated by degumming are removed by water washing; further hydrochloric acid washing is performed to remove organic impurities in the flax fiber, thereby increasing the specific surface area of ​​the flax fiber and the porosity of the flax fiber, thereby obtaining the pretreated flax fiber.

[0019] Modified graphene has high strength and excellent antibacterial properties, and the flax fiber has good air permeability. The modified graphene can be loaded on the surface and internal structure of the flax fiber, which increases the strength and antibacterial properties of the flax fiber. Chitosan is dispersed in an acetic acid solution, and isopropanol is added. Isopropanol and acetic acid form a cosolvent, which further promotes the dissolution and dispersion of chitosan.

[0020] The mixed liquid is sprayed into the mixture. The mixed liquid has a certain viscosity and film-forming property, which can cover the flax fiber, so that the modified graphene can stably adhere to the surface of the flax fiber, increasing the mechanical properties and antibacterial properties of the flax fiber. Chitosan also has good biocompatibility and antibacterial properties. The flax fiber has the characteristics of air permeability and moisture conduction. Chitosan improves the air permeability and moisture absorption of the flax fiber, making it more comfortable and breathable. The high strength characteristics of graphene help to enhance the mechanical strength of non-woven fabrics, making them more durable and wear-resistant.

[0021] Chitosan, modified graphene and flax fiber are subsequently loaded into non-woven fabrics to improve the corresponding performance of the non-woven fabrics. Chitosan provides biocompatibility and antibacterial properties, modified graphene provides improvements in thermal conductivity and strength, and flax fiber provides advantages in natural texture, air permeability and environmental protection. The resulting non-woven fabric has better comprehensive performance.

[0022] Preferably, the mass ratio of the flax fiber, modified graphene and mixed liquid sprayed is 1g:85-90mg:0.05-0.06g.

[0023] By adopting the above technical solution, the mass ratio of the flax fiber, modified graphene and the mixed solution is further limited within a certain range, and the modified flax fiber obtained has excellent mechanical properties, antibacterial properties and air permeability. The modified graphene can be loaded on the surface of the flax fiber and inside the structure, which increases the mechanical properties and antibacterial properties of the flax fiber. The mixed solution has a certain viscosity and film-forming property, which can cover the flax fiber, so that the flax fiber and the modified graphene are tightly bonded, which increases the performance stability of the modified flax fiber. The flax fiber, modified graphene and the mixed solution have a synergistic effect, which is subsequently applied to the impregnation liquid to change the comprehensive performance of the non-woven fabric.

[0024] Preferably, the preparation method of the modified graphene comprises the following steps: dispersing graphene in an ethanol solution, ultrasonically stirring for 25-30 minutes to obtain a graphene suspension; adding lauric acid and sodium alkylphenol polyoxyethylene ether sulfate to the graphene suspension, ultrasonically stirring for 30-60 minutes, filtering, drying, and grinding to obtain graphene powder; dispersing the graphene powder in deionized water, adding nano silver oxide and sodium alginate, stirring at a temperature of 70-75°C for 1-2 hours, drying, and grinding to obtain modified graphene.

[0025] By adopting the above technical scheme, graphene is dispersed in an ethanol solution, and the mechanical effect and thermal effect of ultrasound are utilized to break the van der Waals force between graphene sheets, so that it is better dispersed in the ethanol solution to form a graphene suspension. Lauric acid and sodium sulfate of alkylphenol polyoxyethylene ether are added, and lauric acid improves the dispersibility of graphene in the solution, and interacts with the surface of graphene to change its surface properties. Sodium sulfate of alkylphenol polyoxyethylene ether helps the dispersion of graphene and stabilizes its dispersion state by being adsorbed on the surface of graphene. A surface-modified graphene powder is obtained, which has better dispersibility and stability.

[0026] Graphene powder is dispersed in deionized water, and nano silver oxide and sodium alginate are added. Nano silver oxide has good antibacterial properties and can be loaded on the surface of graphene, improving the dispersibility and stability of graphene, and increasing the antibacterial and mechanical properties of graphene. Sodium alginate has a certain viscosity, so that nano silver oxide can be stably loaded on the surface of graphene, increasing the mechanical properties of graphene and preventing graphene from agglomerating. The obtained modified graphene has better antibacterial and mechanical properties, and is subsequently applied to modified flax fiber to increase the comprehensive properties of flax fiber.

[0027] Preferably, the preparation method of the modified montmorillonite comprises the following steps: (1) dispersing montmorillonite in ethanol, stirring for 1-2 hours, drying, calcining at a temperature of 400-420° C. for 1-2 hours, and then dispersing in deionized water, adding ferric chloride solution, stirring, filtering, and drying to obtain iron-containing montmorillonite; (2) dispersing the modified bamboo powder in deionized water, adding the iron-containing montmorillonite prepared in step (1), stirring at 60-70° C. for 0.5-1 h, filtering, and drying to obtain a mixture; (3) Spraying the gum arabic solution on the surface of the mixture in step (2), drying, and grinding to obtain modified montmorillonite.

[0028] By adopting the above technical solution, montmorillonite is calcined to remove moisture, organic impurities, etc. in the montmorillonite, and its crystal structure and surface properties may be changed, making it easier to react with the ferric chloride added later. The iron ions in the ferric chloride solution can react with the hydroxyl groups or other active sites on the surface of the montmorillonite to form iron-containing montmorillonite. The obtained iron-containing montmorillonite increases the active sites and specific surface area on the surface of the montmorillonite, has enhanced adsorption performance, and is helpful for the subsequent coordination of the montmorillonite with other components.

[0029] The modified bamboo powder is dispersed in deionized water. The modified bamboo powder has moisture absorption and breathability, biodegradability and antibacterial properties. The iron montmorillonite has a strong adsorption capacity and can be loaded on the surface and inside the pores of the modified bamboo powder, thereby increasing the strength and stability of the modified bamboo powder. The gum arabic solution is sprayed on the surface of the mixture. The gum arabic solution has a certain viscosity and can coat the modified bamboo powder, so that the modified bamboo powder and the iron montmorillonite are tightly bonded, thereby increasing the mechanical properties of the overall system. The modified montmorillonite is subsequently applied to the impregnation solution, and can be loaded on the surface of the non-woven fabric, thereby increasing the air permeability, wear resistance, mechanical properties and antibacterial properties of the non-woven fabric.

[0030] Preferably, the mass ratio of the montmorillonite, the modified bamboo powder and the gum arabic solution is 1:0.5-0.7:0.1-0.2.

[0031] By adopting the above technical scheme, the mass ratio of montmorillonite, modified bamboo powder and gum arabic solution is further limited within a certain range, and the obtained modified montmorillonite has better comprehensive performance. Montmorillonite has high strength and stability, and the modified bamboo powder has a porous structure and air permeability. The gum arabic solution has good viscosity and wettability, which helps to better bond the montmorillonite and modified bamboo powder together, thereby increasing the mechanical properties of the montmorillonite. It is subsequently applied to non-woven fabrics to increase the tensile strength, tear strength and other mechanical properties, wear resistance and air permeability of the non-woven fabrics.

[0032] Preferably, the preparation method of the modified bamboo powder comprises the following steps: dispersing the bamboo powder in a sulfuric acid solution, stirring for 1-2 hours, washing with water, and then dispersing it in deionized water, adding dodecyl dimethyl benzyl ammonium chloride, gur gum, and nano-activated calcium carbonate, stirring at a temperature of 80-85°C for 2-3 hours, and drying to obtain modified bamboo powder.

[0033] By adopting the above technical solution, sulfuric acid erodes the surface of bamboo powder particles to a certain extent, removes impurities in bamboo powder, increases the specific surface area of ​​bamboo powder, and makes the surface of bamboo powder rough. Dodecyl dimethyl benzyl ammonium chloride improves the dispersibility and stability of bamboo powder, making bamboo powder uniformly dispersed in deionized water. Nano-active calcium carbonate has good strength and wear resistance, and can be loaded on the pores and surface of bamboo powder particles, increasing the mechanical properties and stability of bamboo powder. Gul gum has a certain viscosity, so that nano-active calcium carbonate is loaded on the surface of bamboo powder particles, improving the mechanical properties of bamboo powder particles, and is subsequently applied to modified montmorillonite, so that the components in montmorillonite are closely combined, thereby subsequently improving the corresponding properties of non-woven fabrics.

[0034] On the second aspect, the present application also provides a method for preparing a water-stopping and breathable composite needle-punched cloth, comprising the following steps: stacking the upper layer, the middle layer, and the lower layer together, compacting them at a temperature of 130-140°C to obtain a composite layer, and then evenly sprinkling 20-40g LDPE powder on the surface of the composite layer, hot pressing at a temperature of 130-140°C, and rolling them up to obtain a composite needle-punched cloth.

[0035] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of the water-stopping and breathable composite needle-punched cloth. The obtained water-stopping and breathable composite needle-punched cloth has good mechanical properties and mechanical strength.

[0036] This application utilizes the air-permeable and water-impermeable properties of PA to produce a waterproof and breathable composite needle-punched fabric with waterproof and breathable functions. It is lighter than traditional needle-punched non-woven fabrics and PVC backing adhesive. LDPE powder and co-extruded film have good adhesion, and the interlayer peeling strength of the composite non-woven fabric is high, which fully meets the use requirements.

[0037] In summary, this application has the following beneficial effects: 1. The upper layer of needle-punched nonwoven fabric in the present application ensures the air permeability of the overall system, so that the gas inside the system can be discharged smoothly, avoiding the accumulation of moisture or heat inside; and the wear resistance of the needle-punched nonwoven fabric can prevent the occurrence of tearing, wear and tear, thereby extending the service life of the overall system.

[0038] 2. The middle layer in this application is a PE / PA / PE co-extruded film, which has good waterproof, moisture-proof and barrier properties. As a waterproof layer, it can effectively block water penetration, ensure the water-stopping performance of the overall system, and block other liquids and impurities to keep the inside of the system clean and dry.

[0039] 3. The lower layer of needle-punched nonwoven fabric in this application increases the overall thickness and strength of the system, providing better support and stability; it can also protect the middle layer of co-extruded film from external damage and extend the service life of the overall system. DETAILED DESCRIPTION

[0040] The present application is further described in detail below with reference to the embodiments.

[0041] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0042] Preparation example of modified flax fiber Preparation Example 1-1 The preparation method of modified flax fiber comprises the following steps: (1) 30 kg of flax fiber was crushed, then dispersed in 50 L of 5% sodium hydroxide solution, stirred at 85° C. for 3 h, washed with water, and then dispersed in 60 L of 1 mol / L hydrochloric acid, immersed at room temperature for 14 h, washed with water, and dried to obtain pretreated flax fiber; (2) dispersing the modified graphene in 100 L of deionized water, adding the pretreated flax fiber of step (1), ultrasonicating for 3 h, filtering, and drying to obtain a mixture; (3) Dispersing 5 kg of chitosan in 10 L of 20% acetic acid solution, adding 1 kg of isopropanol, stirring at room temperature for 8 min to obtain a mixed solution, spraying the mixed solution into the mixture obtained in step (2), and drying to obtain modified flax fiber.

[0043] The mass ratio of charred hemp fiber, modified graphene and mixed liquid spraying is 1g:85mg:0.06g.

[0044] The preparation method of modified graphene comprises the following steps: dispersing 6 kg of graphene in 80 L of ethanol solution, and ultrasonically stirring for 30 min to obtain a graphene suspension; adding 0.5 kg of lauric acid and 0.3 kg of sodium alkylphenol polyoxyethylene ether sulfate to the graphene suspension, and ultrasonically stirring for 60 min, and filtering, drying, and grinding to obtain graphene powder; dispersing the graphene powder in 80 L of deionized water, and adding 1 kg of nano silver oxide and 0.9 kg of sodium alginate, and stirring at a temperature of 75 DEG C for 2 h, and drying, and grinding to obtain modified graphene.

[0045] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified graphene is added.

[0046] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no mixed liquid is added.

[0047] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of the flax fiber, modified graphene and the sprayed mixed liquid is 1g:90mg:0.05g.

[0048] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of the flax fiber, modified graphene and the sprayed mixed liquid is 1g:60mg:0.09g.

[0049] Preparation Example 1-6 The difference from Preparation Example 1-1 is that nano silver oxide is not added in the preparation method of modified graphene.

[0050] Preparation Example 1-7 The difference from Preparation Example 1-1 is that sodium alginate is not added in the preparation method of modified graphene.

[0051] Preparation example of modified montmorillonite Preparation Example 2-1 The preparation method of modified montmorillonite comprises the following steps: (1) 20 kg of montmorillonite was dispersed in 30 L of ethanol, stirred for 2 h, dried, calcined at 420 ° C for 2 h, and then dispersed in 30 L of deionized water, 2 L of ferric chloride solution (concentration of 1 mol / L) was added, stirred at 60 ° C for 1 h, filtered, and dried to obtain iron montmorillonite; (2) dispersing the modified bamboo powder in 90 L of deionized water, adding the iron-containing montmorillonite prepared in step (1), stirring at 70° C. for 1 h, filtering, and drying to obtain a mixture; (3) Spraying the mixture of step (2) with a gum arabic solution, drying, and grinding to obtain modified montmorillonite. 6 kg of gum arabic was dissolved in 15 L of deionized water, and stirred evenly to obtain a gum arabic solution.

[0052] The mass ratio of montmorillonite, modified bamboo powder and gum arabic solution is 1:0.5:0.2.

[0053] The preparation method of modified bamboo powder comprises the following steps: dispersing 20 kg of bamboo powder in 40 L of 7% sulfuric acid solution, stirring for 2 hours, washing with water, and then dispersing in 60 L of deionized water, adding 1 kg of dodecyl dimethyl benzyl ammonium chloride, 2 kg of gur gum, and 5 kg of nano-activated calcium carbonate, stirring at a temperature of 85° C. for 3 hours, and drying to obtain modified bamboo powder.

[0054] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified bamboo powder is added.

[0055] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), no gum arabic solution is added.

[0056] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, modified bamboo powder and gum arabic solution is 1:0.7:0.1.

[0057] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, modified bamboo powder and gum arabic solution is 1:0.1:0.8.

[0058] Preparation Example 2-6 The difference from Preparation Example 2-1 is that guar gum is not added in the preparation method of the modified bamboo powder.

[0059] Preparation Example 2-7 The difference from Preparation Example 2-1 is that in the preparation method of the modified bamboo powder, no nano-active calcium carbonate is added. Example

[0060] Example 1 A water-stopping and breathable composite needle-punched fabric, comprising an upper layer, a middle layer and a lower layer, wherein the upper layer has a gram weight of 100g / m 2 The middle layer is a PE / PA / PE co-extruded film with a thickness of 120μm, and the lower layer is a 200g / m 2 Needle-punched nonwoven fabric; The method for preparing the needle-punched nonwoven fabric comprises the following steps: (1) 65 kg of polyester chips, 8 kg of epoxy linseed oil, 12 kg of calcium carbonate, 1 kg of 2-ethylhexyl para-dimethylaminobenzoate, 2 kg of cerium dioxide, and 1 kg of antioxidant 1010 are uniformly mixed at 70° C. to obtain a polyester fiber raw material, which is melt-spun at 360° C. to obtain polyester fiber filaments, which are combed and web-laid into a non-woven fabric semi-finished product, needle-punched and consolidated, and heat-set to obtain a pre-treated non-woven fabric; (2) The pre-treated non-woven fabric of step (1) is immersed in an impregnation liquid, the temperature of the impregnation liquid is 65° C., the impregnation time is 8 min, and then coagulated, washed with water, dried, and finally oiled to obtain a needle-punched non-woven fabric.

[0061] The spinning temperature is 270°C and the spinning speed is 3500m / min. The yarn is guided by a carding machine to move back and forth on a transmission net at a right angle to the carding machine to lay out and overlap, and then laid on the transmission net to form a non-woven semi-finished product. The non-woven fabric semi-finished product is conveyed to a needle punching consolidation device, which is a needle punching machine. The frequency of the needle punching machine is set to 1000 times / min and the conveying speed is set to 12m / s to obtain a pretreated non-woven fabric. The needle punching needles of the needle punching machine are set to four-corner needles; finally, it is passed through a heat setting device, which is a hot rolling machine. The hot rolling temperature is 120°C for hot rolling setting to obtain a pretreated non-woven fabric.

[0062] Wherein, in step (1), the needle punching machine is used to obtain a weight of 100 g / m 2 Non-woven fabric with a grammage of 200g / m 2 The non-woven fabric is subsequently processed in step (2) to obtain an upper layer material and a lower layer material; The coagulation liquid consists of 30 kg DMF and 70 kg deionized water; The oiling liquid is 5 kg of super-hydrophilic silicone oil SL-310 with a mass fraction of 2%.

[0063] The temperature of the coagulation liquid is 30°C, the temperature of the water washing is 60°C, and the temperature of the drying is 150°C.

[0064] The raw materials of the impregnation liquid include the following components: 25 kg of silane coupling agent KH-560, 19 kg of modified flax fiber, 10 kg of nano titanium dioxide, 22 kg of waterborne epoxy resin curing agent, 15 kg of modified montmorillonite, and 70 kg of deionized water.

[0065] PE / PA / PE co-extruded film was purchased from Guangzhou Huirui Packaging Materials Co., Ltd.

[0066] The method for preparing the above-mentioned water-stopping and breathable composite needle-punched fabric comprises the following steps: The upper layer, the middle layer and the lower layer are stacked together (sent together through a flat laminating device), compacted at a temperature of 130°C to obtain a composite layer, and then 40g of LDPE powder (powder sprinkling device) is evenly sprinkled on the surface of the composite layer, and then hot-pressed at a temperature of 130°C and rolled up to obtain a composite needle-punched cloth.

[0067] The modified flax fiber was prepared by using Preparation Example 1-1, and the modified montmorillonite was prepared by using Preparation Example 2-1.

[0068] Example 2 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that it comprises an upper layer, a middle layer and a lower layer, and the upper layer has a gram weight of 60g / m 2 The middle layer is a 30μm thick PE / PA / PE co-extruded film, and the lower layer is a 400g / m 2 Needle-punched nonwoven fabric; The method for preparing the needle-punched nonwoven fabric comprises the following steps: (1) 66 kg of polyester chips, 7 kg of epoxy linseed oil, 10 kg of calcium carbonate, 1 kg of isooctyl p-dimethylaminobenzoate, 3 kg of cerium dioxide, and 1 kg of antioxidant 1010 are uniformly mixed at 80° C. to obtain a polyester fiber raw material, which is melt-spun at 350° C. to obtain polyester fiber filaments, which are combed and web-laid into a non-woven fabric semi-finished product, needle-punched and consolidated, and heat-set to obtain a pre-treated non-woven fabric; (2) The pre-treated non-woven fabric of step (1) is immersed in an impregnation liquid at a temperature of 60° C. for an immersion time of 5 min, and then coagulated, washed with water, dried, and finally oiled to obtain a needle-punched non-woven fabric.

[0069] Wherein, in step (1), the needle punching machine is used to obtain a weight of 60 g / m 2 Non-woven fabric and weight is 400g / m 2 The non-woven fabric is subsequently processed in step (2) to obtain an upper layer material and a lower layer material; The raw materials of the impregnation liquid include the following components: 20kg of silane coupling agent KH-560, 16kg of modified flax fiber, 6kg of nano titanium dioxide, 18kg of waterborne epoxy resin curing agent, 12kg of modified montmorillonite, and 60kg of deionized water.

[0070] The method for preparing the above-mentioned water-stopping and breathable composite needle-punched fabric comprises the following steps: The upper layer, the middle layer and the lower layer are stacked together (sent together through a flat-plate laminating device), compacted at a temperature of 140°C to obtain a composite layer, and then 20g of LDPE powder (powder sprinkling device) is evenly sprinkled on the surface of the composite layer, and then hot-pressed at a temperature of 140°C and rolled up to obtain a composite needle-punched cloth.

[0071] Example 3 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that the modified flax fiber is prepared using Preparation Example 1-2.

[0072] Example 4 A water-stopping and breathable composite needle-punched fabric is different from Example 1 in that the modified flax fiber is prepared using Preparation Examples 1-3.

[0073] Example 5 A water-stopping and breathable composite needle-punched fabric is different from Example 1 in that the modified flax fiber is prepared using Preparation Examples 1-4.

[0074] Example 6 A water-stopping and breathable composite needle-punched fabric is different from Example 1 in that the modified flax fiber is prepared using Preparation Examples 1-5.

[0075] Example 7 A water-stopping and breathable composite needle-punched fabric is different from Example 1 in that the modified flax fiber is prepared using Preparation Examples 1-6.

[0076] Example 8 A water-stopping and breathable composite needle-punched fabric is different from Example 1 in that the modified flax fiber is prepared using Preparation Examples 1-7.

[0077] Example 9 A water-stopping and breathable composite needle-punched cloth, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Example 2-2.

[0078] Example 10 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Example 2-3.

[0079] Embodiment 11 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-4.

[0080] Example 12 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-5.

[0081] Embodiment 13 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-6.

[0082] Embodiment 14 A water-stopping and breathable composite needle-punched fabric, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-7.

[0083] Comparative Example Comparative Example 1 A waterproof and breathable composite needle-punched fabric, which differs from Example 1 in that no upper layer is added.

[0084] Comparative Example 2 A water-stopping and breathable composite needle-punched fabric, which differs from Example 1 in that no middle layer is added.

[0085] Comparative Example 3 A water-stopping and breathable composite needle-punched fabric, which differs from Example 1 in that no lower layer is added.

[0086] Performance testing The performance of the water-stopping and breathable composite needle-punched fabrics prepared in Examples 1-14 and Comparative Examples 1-3 was tested; The mechanical properties were tested according to GBT 24218.3-2010 "Test methods for textiles - nonwovens - Part 3 - Determination of breaking strength and elongation at break"; the bursting strength was tested according to GB / T 19976-2005 "Determination of bursting strength of textiles - Steel ball method"; According to the second part of GB / T21196.2-2007, the number of frictions when the test sample is worn; According to GB / T5453-85, the air permeability of the sample is tested using a fully automatic fabric air permeability tester. During the test, the sample is placed between the clamps with the dense non-woven fabric layer facing the direction of the airflow. The test area is 30m 2 The circular vent hole was set at 120Pa, the pressure difference was set at 120Pa, the number of tests was 30, and the air permeability was obtained by testing; the test results are shown in Table 1.

[0087] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the water-stopping breathable composite needle-punched fabrics prepared in Examples 1-2 of the present application have good mechanical properties, friction and air permeability, wherein the breaking strength of Example 1 is 86.7MPa, the breaking elongation is 102.36%, the bursting strength is 782N, the number of frictions is 39864, and the air permeability is 3257mm / s. This indicates that the prepared water-stopping breathable composite needle-punched fabrics have good mechanical properties and mechanical strength, and the various components cooperate with each other to achieve the unique functions of being both breathable and water-stopping, and the needle-punched nonwoven fabric has good wear resistance, so that the composite needle-punched fabric has a long service life and can resist external wear and tear.

[0088] In the preparation method of the modified flax fiber of Examples 3-4, modified graphene and the mixed solution are not added respectively, and the mass ratio of the flax fiber, the modified graphene and the mixed solution is changed in Examples 5-6. It can be seen from Table 1 that the test results of the breaking strength, breaking elongation, bursting strength, friction times and air permeability of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding performance test of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1-2 and Example 5, indicating that the modified graphene can be loaded on the surface and inside the structure of the flax fiber, thereby increasing the mechanical properties and antibacterial properties of the flax fiber. The mixed solution has certain viscosity and film-forming properties, and can coat the flax fiber, so that the flax fiber and the modified graphene are tightly bonded, thereby increasing the performance stability of the modified flax fiber. The flax fiber, the modified graphene and the mixed solution have a synergistic effect, which is subsequently applied to the impregnation liquid to change the comprehensive properties of the non-woven fabric.

[0089] In the preparation method of modified graphene in Examples 7-8, nano silver oxide and sodium alginate are not added respectively. As can be seen from Table 1, the test results of breaking strength, breaking elongation, bursting strength, friction times and air permeability of Examples 7-8 are significantly worse than those of Examples 1-2, but better than those of Example 3, indicating that nano silver oxide has good antibacterial properties and can be loaded on the surface of graphene, thereby improving the dispersibility and stability of graphene, and increasing the antibacterial and mechanical properties of graphene; sodium alginate has a certain viscosity, so that nano silver oxide can be stably loaded on the surface of graphene, thereby increasing the mechanical properties of graphene, and the obtained modified graphene has better antibacterial and mechanical properties, which is subsequently applied to modified hemp fiber to increase the comprehensive properties of hemp fiber.

[0090] In the preparation methods of modified montmorillonite in Examples 9-10, modified bamboo powder and gum arabic solution were not added respectively. In Examples 11-12, the mass ratio of montmorillonite, modified bamboo powder and gum arabic solution was changed. As can be seen from Table 1, the test results of breaking strength, breaking elongation, bursting strength, friction times and air permeability of Examples 9-10 were significantly worse than those of Examples 1-2 and Example 11, while the corresponding performance tests of Example 12 were better than those of Examples 9-10, but worse than those of Examples 1-2 and Example 11. Table 1 The results show that the modified bamboo powder has the characteristics of moisture absorption, breathability, biodegradability and antibacterial properties. The iron-containing montmorillonite has a strong adsorption capacity and can be loaded on the surface and inside the pores of the modified bamboo powder, thereby increasing the strength and stability of the modified bamboo powder. The gum arabic solution is sprayed on the surface of the mixture, and the gum arabic solution can coat the modified bamboo powder, so that the modified bamboo powder and the iron-containing montmorillonite are tightly bonded, thereby increasing the mechanical properties of the overall system. Subsequently, the modified montmorillonite can be loaded on the surface of the non-woven fabric, thereby increasing the air permeability, mechanical properties and antibacterial properties of the non-woven fabric.

[0091] In the preparation methods of the modified bamboo powder of Examples 13-14, no gur gum and nano-activated calcium carbonate are added respectively. As can be seen from Table 1, the test results of breaking strength, breaking elongation, bursting strength, friction times and air permeability of Examples 13-14 are significantly worse than those of Examples 1-2, but better than those of Example 9, indicating that the nano-activated calcium carbonate has good strength and can be loaded in the pores and surfaces of bamboo powder particles to increase the mechanical properties and stability of bamboo powder; gur gum allows the nano-activated calcium carbonate to adhere to the surface of bamboo powder particles, improves the mechanical properties of bamboo powder particles, and is subsequently applied to modified montmorillonite, so that the components in the montmorillonite are tightly combined, thereby subsequently improving the corresponding properties of the non-woven fabric.

[0092] Comparative Examples 1-3 do not add the upper layer, middle layer, and lower layer respectively. It can be seen from Table 1 that the test results of the breaking strength, breaking elongation, and bursting strength of Comparative Examples 1-3 are significantly worse than those of Examples 1-2, the number of friction times is not greatly affected, and the air permeability is better, indicating that the three-layer design has better comprehensive performance and realizes multiple functions such as air permeability, water stopping, and wear resistance.

[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A water-stopping and breathable composite needle-punched fabric, characterized in that: It includes upper layer, middle layer and lower layer. The upper layer has a gram weight of 60-100g / m 2 The middle layer is a PE / PA / PE co-extruded film with a thickness of 30-120µm, and the lower layer is a 200-400g / m 2 Needle-punched nonwoven fabric.

2. The waterproof and breathable composite needle-punched fabric according to claim 1, characterized in that: The method for preparing the needle-punched nonwoven fabric comprises the following steps: (1) Mixing polyester chips, epoxy linseed oil, calcium carbonate, isooctyl p-dimethylaminobenzoate, cerium dioxide, and an antioxidant at 70-80° C. to obtain a polyester fiber raw material, melt spinning at 350-360° C. to obtain polyester fiber filaments, combing and web-laying the filaments into a non-woven fabric semi-finished product, needle punching and consolidation, and heat setting to obtain a pre-treated non-woven fabric; (2) The pretreated nonwoven fabric of step (1) is immersed in an impregnation liquid at a temperature of 60-65° C. for 5-8 min, and then coagulated, washed, dried, and finally oiled to obtain a needle-punched nonwoven fabric.

3. The waterproof and breathable composite needle-punched fabric according to claim 2, characterized in that: The raw materials of the impregnation liquid include the following components: 20-25 parts of silane coupling agent KH-560, 16-19 parts of modified flax fiber, 6-10 parts of nano titanium dioxide, 18-22 parts of waterborne epoxy resin curing agent, 12-15 parts of modified montmorillonite, and 60-70 parts of deionized water.

4. The waterproof and breathable composite needle-punched fabric according to claim 3, characterized in that: The preparation method of the modified flax fiber comprises the following steps: (1) crushing the flax fiber, dispersing it in a sodium hydroxide solution, stirring it at a temperature of 80-85° C. for 2-3 hours, washing it with water, and then dispersing it in hydrochloric acid, immersing it at room temperature for 12-14 hours, washing it with water, and drying it to obtain pretreated flax fiber; (2) dispersing the modified graphene in deionized water, adding the pretreated flax fiber of step (1), ultrasonicating for 2-3 hours, filtering, and drying to obtain a mixture; (3) Dispersing chitosan in acetic acid solution, adding isopropanol, stirring at room temperature for 5-8 minutes to obtain a mixed solution, spraying the mixed solution into the mixture obtained in step (2), and drying to obtain modified flax fiber.

5. The waterproof and breathable composite needle-punched fabric according to claim 4, characterized in that: The mass ratio of the flax fiber, modified graphene and mixed liquid sprayed is 1g:85-90mg:0.05-0.06g.

6. The waterproof and breathable composite needle-punched fabric according to claim 4, characterized in that: The preparation method of modified graphene comprises the following steps: dispersing graphene in an ethanol solution, and ultrasonically stirring for 25-30 minutes to obtain a graphene suspension; adding lauric acid and sodium alkylphenol polyoxyethylene ether sulfate to the graphene suspension, and ultrasonically stirring for 30-60 minutes, and filtering, drying, and grinding to obtain graphene powder; and dispersing the graphene powder in deionized water, and adding nano silver oxide and sodium alginate, and stirring at a temperature of 70-75°C for 1-2 hours, and drying, and grinding to obtain modified graphene.

7. The waterproof and breathable composite needle-punched fabric according to claim 3, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: (1) dispersing montmorillonite in ethanol, stirring for 1-2 hours, drying, calcining at 400-420°C for 1-2 hours, and then dispersing in deionized water, adding ferric chloride solution, stirring, filtering, and drying to obtain iron-containing montmorillonite; (2) dispersing the modified bamboo powder in deionized water, adding the iron-containing montmorillonite prepared in step (1), stirring at 60-70° C. for 0.5-1 h, filtering, and drying to obtain a mixture; (3) Spraying the gum arabic solution on the surface of the mixture in step (2), drying, and grinding to obtain modified montmorillonite.

8. The waterproof and breathable composite needle-punched fabric according to claim 7, characterized in that: The mass ratio of the montmorillonite, the modified bamboo powder and the gum arabic solution is 1:0.5-0.7:0.1-0.

2.

9. The waterproof and breathable composite needle-punched fabric according to claim 7, characterized in that: The preparation method of the modified bamboo powder comprises the following steps: dispersing the bamboo powder in a sulfuric acid solution, stirring for 1-2 hours, washing with water, and then dispersing the bamboo powder in deionized water, adding dodecyl dimethyl benzyl ammonium chloride, guar gum, and nano-activated calcium carbonate, stirring at a temperature of 80-85° C. for 2-3 hours, and drying to obtain the modified bamboo powder.

10. The method for preparing a water-stopping and breathable composite needle-punched fabric according to claim 1, characterized in that: The process comprises the following steps: stacking the upper layer, the middle layer and the lower layer together, compacting them at a temperature of 130-140°C to obtain a composite layer, then evenly sprinkling 20-40g of LDPE powder on the surface of the composite layer, hot pressing them at a temperature of 130-140°C, and rolling them up to obtain a composite needle-punched cloth.

Citation Information

Patent Citations

  • Waterproof air-permeable non-woven fabric and production process thereof

    CN105034497A

  • Preparation method for modified graphene

    CN108395736A

  • Antibacterial polyester non-woven fabric and preparation method thereof

    CN108774759A

  • Non-woven fabric dipping liquid for home decoration and preparation method of non-woven fabric dipping liquid

    CN108893988A

  • All-China hemp fiber mask cloth and preparation method thereof

    CN117926500A